Genetic structure and evolutionary dynamics of Babesia gibsoni populations: a cytochrome oxidase subunit I (COXI) gene-based study - Ansu Kumari; Divya Agnihotri; Anil Kumar Nehra; Aman Dev Moudgil; Yudhbir Singh; Prem Sagar Maurya; Devendra Prasad Pateer; Rajat Garg (BMC Veterinary Research)
Abstract Background Babesia gibsoni is a tick-borne intraerythrocytic protozoan parasite causing piroplasmosis in dogs globally. A significant knowledge gap exists regarding the genetic characterization of B. gibsoni using the mitochondrial cytochrome c oxidase subunit I (COXI) gene. To address this, the current study aimed to investigate the genetic diversity and population genetics of B. gibsoni based on COXI gene sequences (≥ 649 bp) in the GenBank. Results Phylogenetic analysis revealed that all B. gibsoni isolates clustered into a single large monophyletic clade based on nucleotide and amino acid sequences, exhibiting high sequence similarity ranging from 98.2–100% at the nucleotide level and 99.1–100% at the amino acid level. Sequence alignment of the COXI gene identified 17 variable sites, including 13 synonymous (T66A, T162C, C177T, T240C, A423G, C426T, G474A, T477C, G486A, T489C, T516C, A531G, and T609A), and four non-synonymous (G138A, C191T, C194T, and G316A) mutations that resulted in amino acid substitutions at four places (M46I, T64I, S65F and V106I). A median-joining haplotype network constructed from the sequences revealed 10 distinct haplotypes, with six of them comprising multiple sequences (2–5 sequences each). No haplotype was shared between any two countries. The Indian population exhibited the highest nucleotide and haplotype diversities, while the Japanese population showed the lowest. Global dataset demonstrated low nucleotide (0.00767 ± 0.00076) and high haplotype (0.911 ± 0.040) diversities. Significant genetic differentiation was observed between Indian and Japanese populations (FST = 0.51910; P < 0.05), with moderate gene flow (Nm = 0.46321) between them. Analysis of molecular variance (AMOVA) revealed that over half of the genetic variation occurred between populations (52.23%), rather than within them (47.77%). Neutrality tests and mismatch distributions suggested that B. gibsoni populations have maintained a constant size. Analysis of the secondary structure of the COXI protein revealed a composition of nine alpha helices, with no beta sheets present. It contained three extracellular domains, five transmembrane domains, and three cytoplasmic domains. Notably, the structure lacked disulfide bonds and signal peptides but featured one N-glycosylation site at position 197. No O-glycosylation sites were detected. Conclusions This study presents the first comprehensive genetic and population-level characterization of B. gibsoni using mitochondrial COXI gene analysis. The findings offer a valuable reference for developing more effective control strategies against canine babesiosis caused by B. gibsoni.